Entangled bodily planning. Developing bodily workshop design for kindergarten teachers' bodily professional knowledge through somatic dance - Ida Pape-Pedersen; Live Strugstad (Cappelen Damm Akademisk NOASP, 2022)
This article explores how a kindergarten teacher educator (Ida) and a somatic dance teacher (Live) collaboratively and bodily planned dance workshops for kindergarten teachers with the aim of developing the kindergarten teachers' bodily professional knowledge. The focus is on the kindergarten teacher educator's and somatic dance teacher's bodily planning process. Methodologically, the article is positioned within arts-based and collaborative research, which is defined under an umbrella of performative research, with the researchers positioned on the inside of the research. The research material is analysed in two layers. The first layer, through Barad's agential realism, results in the creation of four entanglements: to body - to space, to listen - to respond, to rest - to move, to play - to create. These are suggested as design principles. In the second layer, the workshop design is theory infused with Winther's concepts for embodied professional competence. As a result, the authors argue that bodily planning is of high value to really sense what is at stake when aiming at developing workshop design for bodily professional knowledge.